2016
DOI: 10.6004/jnccn.2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Type and Risk of Newly Diagnosed Depression Among Elderly Medicare Beneficiaries With Incident Breast, Colorectal, and Prostate Cancers

Abstract: Background Elderly individuals (age >65 years) with cancer are at high risk for newly diagnosed depression after a cancer diagnosis. It is not known whether the risk of newly diagnosed depression varies by cancer type. Purpose To examine the variations in the risk of newly diagnosed depression by cancer type among elderly individuals with cancer. Methods This study used a retrospective cohort study design and data from the linked SEER-Medicare files. Elderly individuals (age >65 years) with incident breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(57 reference statements)
1
11
1
Order By: Relevance
“…Breast cancer patients feel more depressed ( P =0.046) and distressed ( P =0.017) than patients with colorectal cancer. Our results were contrary to a previous study conducted in the United States that examines the variations of anxiety and depression among the most common cancer types 49. In that study, lung, gynecological, and hematological cancer patients reported the highest levels of distress at the time of cancer diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Breast cancer patients feel more depressed ( P =0.046) and distressed ( P =0.017) than patients with colorectal cancer. Our results were contrary to a previous study conducted in the United States that examines the variations of anxiety and depression among the most common cancer types 49. In that study, lung, gynecological, and hematological cancer patients reported the highest levels of distress at the time of cancer diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…The sample size of the different studies ranged between 42 [ 26 ] and 53,821 [ 27 ] (M = 3904; MD = 252.5; SD = 12,079) (see Table 1 ). This wide range in sample sizes among the different studies is due to the way in which the samples were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The type of cancer present in each sample was highly variable, with some studies selecting people with a specific diagnosis: hematological [ 28 ], gynecologic [ 30 ], non-Hodgkin´s lymphoma [ 26 ], colorectal [ 41 ], gastrointinal [ 45 ], and bladder [ 46 ]; and others including any type of cancer [ 27 , 29 , 32 , 33 , 34 , 37 , 38 , 39 , 40 , 42 , 43 , 44 ]. Despite this variability, breast/gynecological, gastrointestinal, and colorectal cancers were the most represented, with 20.9%, 17.7% and 16.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast, ovarian, prostate, and skin cancer survivors appeared to be in most need of emotional social support. This is likely because people with these cancers had to bear more mental pressure and had a higher risk of also experiencing depression after a new cancer diagnosis [ 38 ]. For skin cancer, the high percentage of companionship indicates that the survivors had many daily struggles that led them to seek out support.…”
Section: Discussionmentioning
confidence: 99%